Changes in Acid-Sulfate Soil Characteristics with Biochar from Various Materials and their Effect on IR-Zinc Production - Abdillah, Muhammad Helmy; Lukmana, Mila; Rahmawati, Linda; Iskarlia, Gusti R. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The extensification of paddy fields is the government's program for food security and nutrition, but it influences the destruction of acid-sulfate soils. This study aimed to assess the improvement result of acid-sulfate soil character applied biochar from local materials with the various doses and to determine the production of IR-Zinc after the treatments, as recommendations for farmers cultivation of IR-Zinc on acid-sulfate soil. The research was conducted in Karang Indah Village, Barito Kuala District, South Kalimantan, from November 2021 to July 2022. The design used was a randomized, complete experiment with two factors: the raw material and the application dose. Research objects consisted of bulk density, porosity, pyrite (FeS2), soil organic-C, number of productive tillers, and weight of dry-milled grain for each treatment. A test using Duncan’s Multiple Range Test (DMRT) at 5% was used to determine the source and dose of biochar that affected significant object changes. The results showed an interaction between raw material and dose levels of biochar. Rice husk biochar increased the yield of IR-Zinc with an application dose of 1.8 kg and improved the characteristics of acid-sulfate soil. Rice husk biochar can provide nutrients due to soil physico-chemical improvements in reducing bulk density and acidity.